Formation of Ruthenium Carbenes by gem-Hydrogen Transfer to Internal Alkynes: Implications for Alkyne trans-Hydrogenation - Leutzsch, Markus (Angew Chem Int Ed Engl, 2015)
Insights into the mechanism of the unusual trans-hydrogenation of internal alkynes catalyzed by {Cp*Ru} complexes were gained by para-hydrogen (p-H(2)) induced polarization (PHIP) transfer NMR spectroscopy. It was found that the productive trans-reduction competes with a pathway in which both H atoms of H(2) are delivered to a single alkyne C atom of the substrate while the second alkyne C atom is converted into a metal carbene. This “geminal hydrogenation” mode seems unprecedented; it was independently confirmed by the isolation and structural characterization of a ruthenium carbene complex stabilized by secondary inter-ligand interactions. A detailed DFT study shows that the trans alkene and the carbene complex originate from a common metallacyclopropene intermediate. Furthermore, the computational analysis and the PHIP NMR data concur in that the metal carbene is the major gateway to olefin isomerization and over-reduction, which frequently interfere with regular alkyne trans-hydrogenation.